Trichoglottis quadriga (Orchidaceae: Epidendroideae: Vandeae: Aeridinae), a new species from Central Highlands of Sri Lanka - Bandara, Champika; Atthanagoda, Anusha Gayan; Peiris, Gayan Prasanga; Jayasundara, Ramitha; Ranasinghe, Bhanuka; Kumara, Udayanga Nuwan; Aberathne, Nimantha; Hettiarachchi, Dushantha; Dissanayake, Malith; Karunathilake, Thimira; Bandara, Niwahal Vimukthi; Fernando, Oshan Dewmith; et al. (Phytotaxa, 2023)
Trichoglottis quadriga is described as a new species from the montane and sub-montane forests, between 900–1800 m elevations in Central Highlands of Sri Lanka. It is morphologically similar to Vietnamese endemic, T. canhii, but differs significantly in having 4-flowered racemes (vs. 5–12-flowered racemes); longer, terete spur, 3.2 mm long and 1.2 mm in diameter with bi-lobed apex (vs. shorter, broadly conical spur, 1.4–1.8 mm long and 1.2–1.5 mm in diameter near the base with roundish apex) and larger labellum, 5.5 mm long and 3.5 mm wide (vs. labellum 3.8–4.0 mm long, 1.8–2.0 mm wide). Colour plates, line drawing and field identification key are provided along with detailed taxonomic description, notes on habitat, ecology and distribution. A preliminary assessment of extinction risk according to the IUCN guidelines is also provided for the new species.